PERAN KADER DALAM PEMANTAUAN KESEHATAN MASYARAKAT DI POSYANDU - Yuniati Yuniati; Lina Handayani; Heni Trisnowati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Health cadres play a vital role in monitoring community health at Posyandu, particularly in promoting better living condition mothers and children at the community level. This papper focus on review the role of health caders in health monitoring. A literature study was conducted on articles published between 2019–2024, analyzing articles from electronic databases such as Google Scholar, PubMed, and Semantic Scholar. After sorting based on inclusion and exclusion criteria, ten relevant articles were selected for further analysis. The study results indicate that Posyandu cadres have significant roles in early disease detection, health data collection, community education, health program implementation, and case referrals to health facilities. However, challenges such as inadequate training, limited resources, and low community participation hinder the optimization of cadre roles. Continuous training support, adequate facilities, and supervision are needed to enhance the effectiveness of health cadres in strengthening primary health systems. This study highlights the importance of health cadres as the forefront of community-based health services in supporting national health programs, particularly in reducing maternal and infant mortality rates.